Localization of wrinkle patterns by crack-tip induced plasticity: Experiments and simulations. (1st December 2019) - Yu, Senjiang; Ma, Long; Zhang, Jingwen; He, Linghui; Ni, Yong
Abstract: Regulating surface wrinkles have received considerable attention because of their potential applications in stretchable electronics, microfluidics, bionics, sensors, stamps, optical devices and smart materials. In this work, optical microscopy and atomic force microscopy revealed that tunable film thickness and substrate stiffness effectively regulate localized wrinkle patterns in metal films deposited on soft polymer substrates. Theoretical analysis and numerical simulation found that the high tensile stress developed during the film deposition leads to channel cracks in the film and creates a stripe-like plastic zone around each crack. The subsequently developed compressive stress in the plastic zone is anisotropic, resulting in the formation of localized straight wrinkles perpendicular to the crack. The width of the wrinkle is consistent with the size of the plastic zone, which decreases with increasing the film thickness or substrate stiffness, in good agreement with the experimental observations. The report in this work not only elucidates how the subtle correlation among crack, plasticity and buckle leads to such localized wrinkling pattern but also demonstrates an efficient way to produce crack-network-guided localized wrinkle patterns.